Tracheotomy During Pandemic COVID-19 Outbreak. Experience At University Clinical Center Tuzla - Šekib Umihanić; Sefika Umihanić; Damir Pištoljević; Rahima Jahić; Dževad Džananović; Samir Kamenjaković (The Turkish Journal of Ear Nose and Throat)
Objective: The aim of the study was to present experience of performed tracheotomies during the Covid19 pandemic and to outline the adjustments made to the procedure for security reasons. Materials and Methods: In the retrospective study for the period March 2020 to April 2022 we analyzed the disease history data and surgical findings from all patients in UCC Tuzla who underwent surgical tracheotomy during the COVID-19 pandemic. Results: 52 patients who underwent open surgical tracheotomy after an invasive mechanical ventilation were analyzed in our study. Group A were 32 COVID-19 consecutive patients (22 male, mean age±13.54 years, range 23-76). The tracheotomy was performed approximately on day 12.4 of the intubation (range 4-28). Group B consisted of 22 patients who had not suffered from COVID-19, and their PCR test was negative for SARSCov-2 (12 male, mean age 59.4±20.40 years, range 19-87). The tracheotomy was performed approximately on day 10.1 of the intubation (range 2-20). There was a statistically significant difference in mortalities when both groups were compared. The most common complication was diffuse bleeding from soft tissue of the neck in the early post tracheotomy period and local infection in the later period. The most common comorbidities were arterial hypertension and diabetes mellitus. Conclusion: According to our study results, COVID-19 elderly patients who are on Invasive Mechanical Ventilation (IMV) have an uncertain prognosis. Correct timing of the tracheotomy is necessary so as not to further traumatize the patients.